SOCIAL, DEMOCRATIC AND COLORED REVOLUTIONS - Ribać, Ivan (The Policy of National Security, 2025)
This text first outlines the sociological and philosophical meanings of the term “revolution,” and then confronts the meaning of this term with the phenomena of “democratic” and “color” revolutions. Unlike the social revolution, neither democratic nor color revolutions imply a radical change in the production of life, and their goals are heterogeneous, because the intentions of the participants and supporters, who are not directly involved in the course of these revolutions, differ. On these grounds, democratic revolutions are analyzed in the countries of the Visegrad Group, particularly in Poland, as well as in the Balkans, with special attention paid to the comparison of the democratic revolutions in Ukraine and Serbia. In this paper, with the help of the previously defined research directions, the following hypotheses are constructed and defended: (1) Color revolutions manifest first in the form of democratic revolutions – in which the political system institutions are called into question; (2) The color revolutions of recent decades primarily had geopolitical goals, as opposed to the preceding period (the end of the previous and the beginning of this century), when they had a transitional peak; (3) Color revolutions cannot be identified with civil disobedience, since there is no solid moral principle at their core, but rather a diffuse justification